CHECKLIST OF FLOWERING PLANTS OF KADABAGATTI FOREST RANGE GOKAK BELAGAVI KARNATAKA - T.C.GOPAL (The Bioscan, 2023)
Gokak is situated in the central part of Belagavi district which is located in northwestern parts of Karnataka, India, maintaining great plant diversity. Little attention to plant diversity studies has been made to it in the past years. Here, we present a checklist of the flowering plants of this region obtained through intensive field investigations and matching of herbarium specimens. In total, 81 species, including one IUCN endangered species and one rare species were documented, belonging to 27 families and 71 genera. The native ranges, habit, habitat, flowering and fruiting and voucher specimens of taxon have been recorded in this checklist. It is the first exhaustive inventory of the flowering plants in Gokak hills which is a significant regional center for plant diversity.